Extremely low risk of hepatocellular carcinoma development in patients with chronic hepatitis B in immune‐tolerant phase. Issue 1 (26th May 2020) - Lee, Han Ah; Lee, Hyun Woong; Kim, In Hee; Park, Soo Young; Sinn, Dong Hyun; Yu, Jung Hwan; Seo, Yeon Seok; Um, Soon Ho; Lee, Jung Il; Lee, Kwan Sik; Lee, Chang Hun; Tak, Won Young; et al.
Summary: Background: Anti‐viral therapy is not indicated for patients with chronic hepatitis B (CHB) in the immune‐tolerant phase. Aims: To investigate the cumulative incidence of phase change and hepatocellular carcinoma (HCC) and independent predictors for phase change in patients with CHB in immune‐tolerant phase. Methods: In total, 946 patients in immune‐tolerant phase, defined as hepatitis B e antigen positivity, HBV‐DNA >20 000 IU/mL and alanine aminotransferase (ALT) ≤40 IU/L, between 1989 and 2017 were enrolled from eight institutes. Results: The mean age of study population (429 men and 517 women) was 36.7 years. The mean ALT and HBV‐DNA levels were 24.6 IU/L and 8.50 log10 IU/mL, respectively. Of the study population, 476 (50.3%) patients remained in immune‐tolerant phase throughout the study period (median: 63.6 months). The cumulative incidence rates of phase change and HCC at 10 years were 70.7% and 1.7%, respectively. Multivariate analyses revealed that HBV‐DNA level >10 7 IU/mL was associated independently with a reduced risk of phase change (hazard ratio [HR] = 0.734, P = 0.008), whereas a high ALT level, above the cut‐off recommended in the Korean Association for the Study of the Liver guidelines (34 IU/L for men and 30 IU/L for women), was associated independently with a greater risk of phase change (HR = 1.885, P < 0.001). Conclusions: The criterion of HBV‐DNA level > 10 7 IU/mL may be useful to define immune‐tolerant phase. In addition, an extremely low risk of HCC development was observed in patients with CHB in immune‐tolerant phase. Abstract : LINKED CONTENT This article is linked to Hsu and Huang et al paper. To view this article, visit https://doi.org/10.1111/apt.15798 .